(untitled) (Journal of humanities and social sciences exploratio, 2025)
Based on the Buddhist "Perfect Teaching" system, this paper attempts to construct an Ontology-Existenziology system rooted in the "Emptiness of the Being itself (第一义空)", in response to the existential predicament of homelessness faced by modern individuals. Through a comparative analysis of the "Separate Teaching (别教)" and the "Perfect Teaching (圆教)", the paper reveals the limitations of the "Separate Teaching" which reifies emptiness into a secondary meaning (第二义空) and constructs a system based on the separation of the true and the false. It further elucidates how the "Perfect Teaching", through the deconstructive construction of "Separation-as-(Non-)Separation As (Non-)Separation (别别为别)", returns to the Ontology-Existenziology of "Separate Nature (别性)" as the suchness-presence of the Emptiness of the Being itself. On this basis, the paper further proposes "the Problem (问题)" as the root of the Existenz of Separate Nature. Drawing from the system foundation of the "Karmic Organism - Inherent Nature Possessing All Things (机缘整体-性具万物)" derived from the interpretation of the Huayan Perfect Teaching, it constructs an organic system focused on "the Problem". This system not only loads "things (Existents)" and "life (the I, as the Existenz that projects how to exist)" with meaning and weight, but also provides a foundation for metaphysics based on an organic system grounded in "Emptiness (空性)".